2009
DOI: 10.1007/s00018-009-0189-x
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase inhibitors as therapeutics: from pan inhibition to isoform selectivity

Abstract: The emerging critical implications of Rho/Rho-kinase (ROCK) signaling in neurodegenerative diseases, glaucoma, renoprotection, diabetes and cancer have sparked growing interest in the pharmacological potential of ROCK inhibitors beyond their current application in cardiovascular disease. This article discusses the therapeutic benefits of novel ROCK inhibitors in development, and highlights the recent advances in the current understanding of disease-dependent and isoform-specific functions of ROCK and their pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 90 publications
2
110
0
Order By: Relevance
“…Also, we showed that the distribution patterns of ROCK1 and ROCK2 differed in both porcine oocytes and embryos by using immunostaining employing specific antibodies. Although ROCK1 and ROCK2 share structural similarities, being 65% homologous in terms of amino acid sequence (92% homologous in the kinase domains), the two proteins may play distinct roles in cell differentiation and adhesion (Lock & Hotchin 2009, Hahmann & Schroeter 2010. In a previous study in mitotic cells, Values with different superscripts (*, †, ‡) indicate that the numbers are significantly different (P!0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we showed that the distribution patterns of ROCK1 and ROCK2 differed in both porcine oocytes and embryos by using immunostaining employing specific antibodies. Although ROCK1 and ROCK2 share structural similarities, being 65% homologous in terms of amino acid sequence (92% homologous in the kinase domains), the two proteins may play distinct roles in cell differentiation and adhesion (Lock & Hotchin 2009, Hahmann & Schroeter 2010. In a previous study in mitotic cells, Values with different superscripts (*, †, ‡) indicate that the numbers are significantly different (P!0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we proposed the hypothesis that LPA enhanced embryo development by activating ROCKs. Y27632, a specific inhibitor of Rho-kinases (Ishizaki et al 2000, Hahmann & Schroeter 2010, has been widely used to study enzyme function. Therefore, employing either Y27632, a specific inhibitor of ROCKs, or LPA, an activator of ROCKs, we explored the distribution and function of ROCK1 and ROCK2 during porcine oocyte maturation and embryonic cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of Rho signaling by PCP results in downstream activation of the serine/threonine Rho-associated coiled coil-containing protein kinases (ROCK)1 and ROCK2 (9). ROCK1 and ROCK2 phosphorylate downstream substrates such as myosin light chain and LIM kinases 1/2, which further regulate a range of cellular functions primarily through rearrangement of the actin cytoskeleton (10,11). ROCK is dysregulated in a variety of cancers, including prostate, breast, and lung cancers, with ROCK overexpression contributing to metastasis by enhancing tumor cell invasion and motility (11).…”
mentioning
confidence: 99%
“…Nevertheless, the current findings suggest that Rac1 inhibition may be accomplished directly in vivo because of the favorable safety profile of NSC23766, as observed in our mouse model of streptozotocin‐induced diabetes mellitus. Finally, the effects of LY27632 as ROCK1 inhibitor can be also attributed, in part, to the inhibition of ROCK2, although recent studies have demonstrated that ROCK1 and ROCK2 have distinct nonredundant functions and have different targets in different cell types 45, 46…”
Section: Discussionmentioning
confidence: 99%